Effect of Ashwagandha, Turmeric and Antibiotic on Blood Biochemical Profile of Repeat Breeding Gir Cows with Subclinical Endometritis - V. Vadher, Dhruv; S. Parikh , Suryakant; K. Sharma, Arun; P. Vijyeta, Hardipsinh; N. Thummar, Meet; R. Ram, Dilip (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The present study was conducted to evaluate the influence of ashwagandha and turmeric on blood biochemical profile in subclinical endometritis (SCE) affected repeat breeding Gir cows. Thirty apparently healthy repeat breeder Gir cows, aged 4 to 8 years (>90 days in milk) and positive for SCE on cytobrush technique, were selected from the University Farm and nearby areas of Junagadh region. They were randomly divided into 5 equal groups. In Group A (positive control), cows were administered 30 mL of normal saline intrauterine (I/U) as a single dose. Group B received 30 mL of moxifloxacin I/U for 3 consecutive days. In Group C and D, cows were treated with 5 mL of ashwagandha and 5 mL of turmeric extract diluted in 30 mL of distilled water, respectively, while Group E received a combination treatment of 5 mL each of ashwagandha and turmeric extract, diluted in 30 mL of distilled water and administered I/U for 3 consecutive days. Blood samples collected at estrus before treatment (0 hr) and at subsequent estrus after treatment were compared for changes in blood biochemical profile. Following treatment, significant increase (p0.05). The highest first service conception rate was observed in the group treated with the combination of ashwagandha and turmeric extract (66.66%), followed by turmeric extract alone (50.00 %), ashwagandha extract alone (33.33%) sensitive antibiotic (33.33%), and control (0.00%). The study revealed that a combination of ashwagandha and turmeric extract has best therapeutic efficacy and can be used as an alternative therapy for the treatment of subclinical endometritis in repeat breeding cows.